FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN AUDITOR UNTUK MENERIMA PERIKATAN - Thamrin, Tamadoy; Mulyadi E. S, dan Ratno (Journal of Accounting and Strategic Finance, 2010)
In order to distribute the fund of economic machine to the public into productive businesses that is efficiently and effectively operated, hence the reliable of financial information is required. Public accountant is in charge to lift the reliability level of financial statement of enterprises thus they would obtain reliable of financial statement. Accountant public had to consider a number of influential factors prior to accept an engagement from clients.This research is using the primary data through questioner to the auditors who are working at public accountant office in east Surabaya with the total auditors are 75. The obtained data has been cultivated by using SPSS 15.0 to multiple regression analysis. In order to weigh up the proposed hypothesis, researcher used t test to crosscut partially influence on research variables and F test to crosscut simultaneously influence.Through the result of analysis concluded that Auditor Competency and Audit Fee are influenced to accountant public to accept the audit engagement. Partially, only auditor competency influenced. Thus the proposed hypothesizes are truly proven. Keywords         : kompetensi auditor (auditor competency), audit fee, keputusan untuk menerima perikatan (the decision to accept audit engagement)